Fundraising and E-Commerce for Products Student Entrepreneurship for Financial Independence Tarbiyatul Ummah Sukoharjo Islamic Boarding School: Penggalangan Dana dan E-Commerce Produk Kewirausahaan Santri untuk Kemandirian Finansial di Pondok Pesantren Tarbiyatul Ummah Sukoharjo - Muqorobin, Muqorobin Muqorobin; Sumadi, Sumadi Sumadi; Fitria, Tira Nur (Universitas Lancang Kuning, 2024)
This Community Service activity aims to train students' entrepreneurship for financial independence at the Tarbiyatul Ummah Sukoharjo Islamic Boarding School. The service activity method used is lectures to provide theory about entrepreneurship, design, product photography, e-commerce, and fundraising management, as well as training practical skills such as product design using PowerPoint and Canva photos and editing product photos with applications, snack packaging. , introduction and use of social media or e-commerce platforms, for example Facebook, Instagram, Shopee and TikTok. This training includes creating packaged product content, marketing via an e-commerce website called https://tumbaso.com/, and fundraising management. This activity was held in several meeting sessions outside and inside the Islamic Boarding School and involved 10 students, 5 ustadz, and a team from the AAS Indonesia Business Technology Institute. Training and even developing an e-commerce website that is integrated with social media and Search Engine Optimization (SEO) is expected to make marketing and financial management of Islamic boarding schools easier, thereby increasing the effectiveness of sales and financial management.